Design, Synthesis and Characterization of Novel Amine Derivatives of 5-[5-(Chloromethyl)-1, 3, 4-Oxadiazol-2-yl]- 2-(4-Fluorophenyl)-Pyridine as a New Class of Anticancer Agents - Vinayak, Adimule; Sudha, Medapa; Lalita, Kumar S (Dhaka University Journal of Pharmaceutical Sciences, 2017)
A linear strategy was adopted in synthesizing the novel amine derivatives 7(a-h) of 5-[5- (chloromethyl)-1, 3, 4-oxadiazol-2-yl]-2-(4-fluorophenyl)-pyridine (6) and screened these compounds for in vitro anticancer activity against three human cancer cell lines (HeLa,Caco-2 and HepG2). The synthesised novel compounds were characterized by 1H NMR, MS and 13C NMR spectroscopic evidences. Microwave irradiation of compound (5) in presence of chloroacetyl chloride and phosphoryl oxychloride yielded the dehydrated cyclized key intermediate 5-[5-(chloromethyl)-1,3,4-oxadiazol-2-yl]-2-(4-fluorophenyl)-pyridine which upon treatment with various primary or secondary amines (a-h) resulted into the corresponding amine derivatives. The IC50 values of the final compounds were compared with that of 5-fluorouracil (5-FU) taken as the standard. Compounds 7a and 7d were found to be highly cytotoxic against HepG2 cell lines with IC50 values of 2.6 ?M (IC50 = 34.0 ± 0.5 ?M) and 5.8 ?M (IC50 = 112 ± 1.4 ?M) respectively. The compound (7f) alone was found to have high cytotoxicity against Caco-2 cell lines with IC50 value of 2.3 ?M (IC50 = 87 ± 2.6 ?M). Dhaka Univ. J. Pharm. Sci. 16(1): 11-19, 2017 (June)